Torsional vibration-considered energy management strategy for power-split hybrid electric vehicles. (10th May 2021) - Wang, Feng; Xia, Jiaqi; Xu, Xing; Cai, Yingfeng; Ni, Shaoyong; Que, Hongbo
Abstract: The development of planetary gear hybrid powertrain (PGHT) in recent years has targeted at the fuel economy for hybrid electric vehicles. However, added complexity and flexibility brought by hybridized powertrain have lead to the increase of vibration and noise. In order to achieve a satisfying energy economy and ride comfort, this paper presents a torsional vibration-considered energy management strategy (TV-EMS) for PHEVs. Firstly, a torsional vibration model of PGHT is developed to observe the vibration behavior in different operating modes and help to develop the energy management strategy. Specifically, root mean square map of the powertrain vibration excited by engine ripple torque and angle-varying meshing stiffness of epicyclic gear are investigated by a lumped-parameter torsional vibration model, the maximum root mean square value of PGHT vibration in power-split mode is 35.8 m/s 2 . A multi-objective energy management strategy is then proposed to cope with the control objective of suppressing torsional vibration and reducing energy consumption. Finally, by means of simulation and hardware-in-the-loop test, it is concluded that the fuel consumption of TV-EMS increases slightly (by 2.5%) than that of ECMS, while the torsional vibration of PGHT is significantly reduced (by 25%), and the proportion of working points in resonance region is reduced from 3.8% to 1.0%. Highlights: Root mean square map of the powertrain vibration was derived from lumped-parameter model. Fuel consumption of TV-EMS increased slightly (by 2.5%) than that of ECMS. Torsional vibration level decreased significantly (by 25%) with TV-EMS.